The Palestinian Refugees, International Law, and the Peace Process - Sabel, Robbie (Refuge: Canada’s Journal on Refugees, 2003)
The article reviews recent Israel-Palestinian negotiations on the issue of the Palestinian refugees. It examines legal aspects of the major issues that were involved in the negotiations including who was responsible for the plight of the refugees, the definition of who is a refugee, the existence of a right of return, and the question of restitution and compensation. The article reaches the conclusion that, in the context of the Arab-Israeli conflict, no legal “right of return” exists, implementation of such a right would be impracticable and UN General Assembly Resolution 194 does not impose such a right. The article shows, however, that despite deep differences on legal positions, the parties have endeavoured to draft language that will enable them to proceed with a practical solution.